When business kills : the emerging crime of corporate manslaughter - Field, Sarah (Business law collection., 2018)
This book aims to explain in clear, accessible language the approach taken by government to corporate offending resulting in a fatality in both the United Kingdom and the United States. The key provisions of the statutory offence of corporate manslaughter, introduced into the United Kingdom in 2008, are examined, and set in context through a consideration of their relationship with prosecution for fatalities at work via the Health and Safety at Work etc Act 1974. Further contextualization is made through comparison with the current position in the United States, highlighting both similarities and differences in approach to occupational fatalities. The range of potential penalties is discussed with particular focus on the sentencing guidelines that apply after February 2016. Concluded corporate homicide cases are reviewed in order to assess the current regime in terms of financial penalties and to shine light on the evolving approach of the prosecuting authorities and the courts to these offenses.